A Case Study: The Inclusion of Teaching Grammar in ESP Speech Course At Accounting Departement – State Polytechnic of Malang - R. Setiawan; Lia Agustina (Universitas Muhammadiyah Semarang, 2022)
The importance of teaching grammar in the English language has long been debated. Theorists and practitioners agreed that it is important to obtain knowledge in language that cannot be separated. However, a review of this ongoing controversy has revealed the importance of grammar instruction and its significance in language learning and improvement. All four skills of language mastery are influenced by grammar instruction. Although the benefits of teaching grammar include improving writing ability, it also has an impact on reading, listening, and speaking skills, and it is now well recognized. A high level of grammatical competence would necessitate improved oral communication skills. Grammar knowledge and application, as well as the use of suitable punctuation, would be included in communicative and writing proficiency. To portray meanings in appropriate expressions, the language's vocabulary is used. It will explain why grammar instruction is important and how it has been included into language acquisition. The researchers conducted a qualitative case study research design with discussed general mistakes of students made from the assignments given. 32 students of The Accounting Department of State Polytechnic of Malang used as the subject of the research.